STRATEGI RESPON KRISIS PEMERINTAH TERHADAP KASUS AKSI DEMONSTRASI TUNJANGAN DPR: ANALISIS ISI KUANTITATIF PADA PEMBERITAAN MEDIA - Shafira Ayyu Listia Azizah; Dian Purworini (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study discusses the crisis response strategies employed by the Indonesian government in handling demonstrations related to the policy on allowances for members of the House of Representatives. Using the Situational Crisis Communication Theory (SCCT) approach, this study was conducted using a descriptive quantitative content analysis methodology. The units of analysis in this study were taken from every news item published in the media during the period from August to September 2025. The results show that in facing the crisis, the government used the attack the accuser strategy 20% of the time, scapegoat 20%, compensation 20%, reminder 15%, justification 12.5%, and ingratiation 12.5%. Meanwhile, the denial, excuse, apology, and victimization strategies were not found in the news. From the difference test results, it can be concluded that there is no significant difference in the use of response strategies in various media, where the government tends to combine defensive and accommodative strategies to minimize responsibility while reducing escalation. The results of this study provide an understanding of the dynamics of government responses when facing public pressure and serve as a reference for the government in managing its reputation during policy conflicts.